2020
DOI: 10.3390/molecules25153316
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Up Design Approach for OBOC Peptide Libraries

Abstract: One-bead-one-compound peptide libraries, developed following the top-down experimental approach, have attracted great interest in the identification of potential ligands or active peptides. By exploiting a reverse experimental design approach based on the bottom-up strategy, we aimed to develop simplified, maximally diverse peptide libraries that resulted in the successful characterization of mixture components. We show that libraries of 32 and 48 components can be successfully detected in a single run using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…The R package Peptides was used to calculate the aa composition of peptides, expressed in mole percentage (mol%). The aa are categorized based on their intrinsic properties into 11 subcategories: Tiny (Ala, Cys, Gly, Ser, Thr), Small (Ala, Cys, Asp, Gly, Asn, Pro, Ser, Thr, Val), Aliphatic (Ala, Ile, Leu, Val), Aromatic (Phe, His, Trp, Tyr), Nonpolar (Ala, Cys, Phe, Gly, Ile, Leu, Met, Pro, Val, Trp, Tyr), Polar (Asp, Glu, His, Lys, Asn, Gln, Arg, Ser, Thr), Charged (Asp, Glu, His, Lys, Arg), Basic (His, Lys, Arg), Acidic (Asp, Glu), Sulfur (Cys, Met), and Hydroxylic (Ser, Thr).…”
Section: Methodsmentioning
confidence: 99%
“…The R package Peptides was used to calculate the aa composition of peptides, expressed in mole percentage (mol%). The aa are categorized based on their intrinsic properties into 11 subcategories: Tiny (Ala, Cys, Gly, Ser, Thr), Small (Ala, Cys, Asp, Gly, Asn, Pro, Ser, Thr, Val), Aliphatic (Ala, Ile, Leu, Val), Aromatic (Phe, His, Trp, Tyr), Nonpolar (Ala, Cys, Phe, Gly, Ile, Leu, Met, Pro, Val, Trp, Tyr), Polar (Asp, Glu, His, Lys, Asn, Gln, Arg, Ser, Thr), Charged (Asp, Glu, His, Lys, Arg), Basic (His, Lys, Arg), Acidic (Asp, Glu), Sulfur (Cys, Met), and Hydroxylic (Ser, Thr).…”
Section: Methodsmentioning
confidence: 99%
“…Their method showed that genetic algorithms can optimize the library search with the highest number of peptides based on multiple objectives such as chemical and mass diversity. Their system could be extended to other search objectives and their combinations as they've later shown by introducing a sequence‐based property evaluation step, such as polarity, hydrophobicity and/or H‐bonding [36] . Their work opens up the possibilities of user‐defined, rationally designed peptide libraries by exploring the sequence space in an informed and targeted way.…”
Section: Computational Approaches For Screening Peptide Spacesmentioning
confidence: 99%
“…12,13 By incorporating the diversity parameter into the evolutionary process, we emphasized the intra-library diversity, which makes individual peptides distinguishable by mass spectrometry. 14 The peptides were represented as strings, i.e., sequences of amino acid single letter codes, matching the FASTA format. Novel ML methods, mainly generative adversarial networks and variational autoencoders, present an alternative to genetic algorithms as a means of generating novel peptides exhibiting specific activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Genetic algorithms have been used to construct therapeutic, bactericidal, and antimicrobial peptides. In our previous work, we have presented a genetic algorithm adaptation and parametrization for exploring the chemical space of short peptides using random peptide libraries. , By incorporating the diversity parameter into the evolutionary process, we emphasized the intra-library diversity, which makes individual peptides distinguishable by mass spectrometry . The peptides were represented as strings, i.e., sequences of amino acid single letter codes, matching the FASTA format.…”
Section: Introductionmentioning
confidence: 99%